The Power of Proximity to Coworkers - Natalia Emanuel; Emma Harrington; Amanda Pallais (The Quarterly Journal of Economics, 2026)
Abstract How does proximity to coworkers affect training and productivity? We study software engineers at a Fortune 500 firm from 2019 to 2024, leveraging two shocks to proximity: the office closures in 2020 and the subsequent return-to-office mandates in 2022 and 2023. In both cases, co-located teams experienced bigger changes in proximity than distributed ones, facilitating difference-in-differences designs. We find that sitting near teammates increases coding feedback by 18.3% and improves code quality. Gains are concentrated among less-tenured and younger employees, who are building human capital. However, there is a trade-off: experienced engineers write less code when sitting near teammates. In national U.S. data, we find evidence that the rise of remote work has had scarring effects on young college graduates. In remotable jobs, young graduates’ unemployment rate increased relative to older graduates’ post-pandemic (2022–2024) compared to pre-pandemic (2017–2019), a pattern we do not observe in non-remotable jobs.